The Influence of Green Human Resource Management Practices on Corporate Environmental Performance through the Mediation of Pro-Environmental Behavior Moderated by Environmental Knowledge - Surahman, Septiansyah; Andriyani, Andriyani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze the effect of Green Human Resource Management (GHRM) practices on the environmental performance of companies with Pro-Environmental Behavior as a mediator and Environmental Knowledge as a moderator. The research problem arises from the gap in previous studies on the impact of GHRM practices on environmental performance. The research objectives are to analyze the effect of GHRM practices on environmental performance, pro-environmental behavior, and the mediating role of pro-environmental behavior on the relationship between GHRM practices and environmental performance. The study also aims to analyze the moderating role of environmental knowledge on the relationship between GHRM practices and pro-environmental behavior. The research method used is a survey with a sample of employees from PT Kalbe Farma, a pharmaceutical company in Indonesia. The study found that GHRM practices have a positive effect on environmental performance, pro-environmental behavior, and the mediating role of pro-environmental behavior on the relationship between GHRM practices and environmental performance. The study also found that environmental knowledge moderates the relationship between GHRM practices and pro-environmental behavior. The practical benefit of this research is to provide a reference for organizations in formulating strategies to achieve optimal environmental performance. The theoretical benefit is to contribute to the development of knowledge in the field of human resource management. The study adopts the Ability-Motivation-Opportunity (AMO) theory and the six dimensions of GHRM practices, namely green recruitment and selection, feedback, green self-efficacy, leadership role, organizational culture, and employee empowerment.